SUBJECT AND AUTHOR INDEXS - IJBE Volume 1 (School of Business, IPB University (SB-IPB), 2015)
SUBJECT INDEX IJBE VOLUME 1EPA, 1Agrotourism, 148AHP, 148balance scorecard, 63batik tulis Rolla Junior, 23Broiler, 90business model canvas, 137business performance,32capital structure, 81cashew industry,158CHAID,106CLI,42coal transportation service,63company’s characteristics, 81competitive advantage, 12competitive strategy, 127consumer satisfaction, 51CSI, 42customer loyalty, 42customer satisfaction,42decision of visitors, 72development strategy, 23development,158entrepreneurship, 32Feasibility studies, 90FEM, 81gap analysis, 1Indonesia Stock Exchange, 177Indosat, 137investor,177Kawah Putih, 72kedai sop durian lodaya (KSDL),51klassen typology, 96leading sector, 96less cash society, 137liquidity ratio, 165location quotient, 96logistic regression, 115market, 177marketing development strategy, 148Marketing mix, 72mobile payment, 137modern and Traditional cage, 90multiple regression analyse,165multiple regression, 177net working capital, 165organic tofu product, 115Padang, 106paired comparison, 63partnership, 1, 32Pecking Order Theory, 81PLS, 81Portfolio, 96power, 32product quality, 51profitability ratio, 165Prol Tape Primadona, 127purchase decision, 115purchase intention, 51purchasing interest,115QSPM, 23, 127refilled drinking water, 106seed,1segmentation, 106SEM, 42, 51service quality, 51SMEs, 96specialty coffee, 12stock,177strategic diagnosis,137strategy, 158Sukorambi Botanic Garden, 148SWOT, 23, 127, 148, 158SWOT-AHP, 12tourists,72UD. Primadona, 127value chain, 12VRIO,12 AUTHOR INDEX IJBE VOLUME 1Adiningsih, Kartika Puspitasari,42Aknesia, Vharessa,12Amalia, Firda Rachma,90Andati, Trias, 177Anggraeni, Lukytawati,23Asriani,158Daryanto, Arief,12, 90Djamaludin, MD., 42Djohar, Setiadi,96Fachrodji, Achmad,72Fahmi, Idqan,1, 63, 127Fasyni, Awisal,106Hubeis, Musa,148Iskandar, Dodi,51Juanda, Bambang, 165Kirbrandoko, 12, 106, 115Lumbantoruan, Dewi Margareth,96Maulana, TB Nur Ahmad,81Muksin, 148Mukti Soleh, Cecep,63Najib, Mukhamad,106Noor, Tajudin,81Nugroho, Tantry,115Nurmalina, Rita, 42, 51Nurul Huda, Ghulam, 177Oktaviani, Rina, 32, 137Prasetyo, Dian Widi,1Putra, Adetiya Prananda, 127Rachmina, Dwi, 165Rahayu, Isyana,72Riani, Etty,51Ridho Nurrochmat, Dodik,72Ridwansyah, Fauzi,137Rizal, 32Rujito, Hari,90Saptono, Imam Teguh,137Sartono, Bagus,96Sinaga, Bonar M., 177Sinaga, Bonar,81Sucipto, Edi, 32Sumantri, Maman, 165Sumarwan, Ujang,115Suryadi, Ujang,23Suryani, Indah Eko, 23Teguh Saptono, Imam,63Wibisono, Yossi,1, 127Wijayanti, Tantri, 148